Expectations and experiences of investigators and parents involved in a clinical trial for Duchenne/Becker muscular dystrophy. (February 2014) - Peay, Holly L; Tibben, Aad; Fisher, Tyler; Brenna, Ethan; Biesecker, Barbara B
Background: The social context of rare disease research is changing, with increased community engagement around drug development and clinical trials. This engagement may benefit patients and families but may also lead to heightened trial expectations and therapeutic misconception. Clinical investigators are also susceptible to harboring high expectations. Little is known about parental motivations and expectations for clinical trials for rare pediatric disorders. Purpose: We describe the experience of parents and clinical investigators involved in a phase II clinical trial for Duchenne and Becker muscular dystrophy: their expectations, hopes, motivations, and reactions to the termination of the trial. Methods: This qualitative study was based on interviews with clinical investigators and parents of sons with Duchenne and Becker muscular dystrophy (DBMD) who participated in the phase IIa or IIb ataluren clinical trial in the United States. Interviews were transcribed and coded for thematic analysis. Results: Participants were 12 parents of affected boys receiving active drug and 9 clinical investigators. High trial expectations of direct benefit were reported by parents and many clinicians. Investigators described monitoring and managing parents' expectations; several worried about their own involvement in increasing parents' expectations. Most parents were able to differentiate their expectations from their optimistic hopes for a cure. Parents' expectations arose from other parents, advocacy organizations, and the sponsor. All parents reported some degree of clinical benefit to their children. Secondary benefits were hopefulness and powerful feelings associated with active efforts to affect the disease course. Parents and clinical investigators reported strong, close relationships that were mutually important. Parents and clinicians felt valued by the sponsor for the majority of the trial. When the trial abruptly stopped, they described loss of engagement, distress, and feeling unprepared for the possibility of trial termination. Limitations: This was a retrospective study of one clinical trial. We were unable to recruit participants whose children received placebo. The interviews occurred during a time of significant uncertainty and distress for many of the participants. Conclusion: This pilot study reflects complex outcomes of strong community engagement. The findings highlight a need for renewed education about, and support for, clinical trial termination and loss of drug access. The primary positive outcome was demonstration of strong relationships among committed parents and study teams. These relationships were highly valued by both parties and may suggest an ideal intervention opportunity for efforts to improve psychological well-being. A negative outcome attributed, in part, to community engagement was inappropriately high trial expectations. More optimistically, high expectations were attributed, in part, to the importance of hope and powerful feelings associated with active efforts to affect the disease course.